SiGe HBTs Optimization for Wireless Power Amplifier Applications. (29th December 2010) - Mans, Pierre-Marie; Jouan, Sebastien; Fregonese, Sebastien; Vandelle, Benoit; Pache, Denis; Arnaud, Caroline; Maneux, Cristell; Zimmer, Thomas
Abstract : This paper deals with SiGe HBTs optimization for power amplifier applications dedicated to wireless communications. In this work, we investigate the fT -BVCEO tradeoff by various collector optimization schemes such as epilayer thickness and dopant concentration, and SIC and CAP characteristics. Furthermore, a new trapezoidal base Germanium (Ge) profile is proposed. Thanks to this profile, precise control of Ge content at the metallurgical emitter-base junction is obtained. Gain stability is obtained for a wide range of temperatures through tuning the emitter-base junction Ge percent. Finally, a comprehensive investigation of Ge introduction into the collector (backside Ge profile) is conducted in order to improve the fT values at high injection levels.